2010
DOI: 10.4314/njm.v19i1.52485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low intensity continuous training programme on serum uric acid in the non pharmacological management of hypertension: a randomized controlled trial

Abstract: Background: Method: Results: Conclusion: Elevated serum uric acid (SUA) is considered to be positively associated with cardiovascular event risk factor in hypertension. Also, the positive role of exercise in the management of Hypertension has been well and long established. However the relationship between SUA level and hypertensive management particularly in non pharmacological technique is ambiguous and unclear. Therefore the purpose of the present study was to determine the effect of continuous low intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…8 In this present study there is significant difference between urea and uric acid level in pre and post exercise conditions in males although in females no significant alteration seen in pre and post exercise levels. Significant change in levels of uric acid after exercise program in middle age females is reported by Bijeh N et al 9 Some of the studies, 10,11,12 also reported increase in uric acid where as other studies 11 have opposite observations. Vanita Lal et al observed increase in creatinine level due to aerobic exercises in absence of renal damage.…”
Section: Discussionmentioning
confidence: 87%
“…8 In this present study there is significant difference between urea and uric acid level in pre and post exercise conditions in males although in females no significant alteration seen in pre and post exercise levels. Significant change in levels of uric acid after exercise program in middle age females is reported by Bijeh N et al 9 Some of the studies, 10,11,12 also reported increase in uric acid where as other studies 11 have opposite observations. Vanita Lal et al observed increase in creatinine level due to aerobic exercises in absence of renal damage.…”
Section: Discussionmentioning
confidence: 87%
“…Of those, 298 articles were excluded including 13 articles on studies to treat heart failure, 7 articles on coronary heart diseases and 76 articles on pharmacotherapy for hypertension (see list of excluded studies in the online supplemental material 1). Twenty-three studies (reported in 42 articles)24–66 on non-pharmacological strategies to treat patients with hypertension matched the inclusion criteria and were included in this systematic review (figure 1 and list of included studies in the online supplemental material 2). The characteristics and main results of these studies were summarised in table 2.…”
Section: Resultsmentioning
confidence: 99%
“…For example, high-intensity interval training (HIIT), which is gaining popularity, is characterized as an effective program through which the effects of some non-communicable chronic diseases, including type 2 diabetes and hypertension, can be reduced [4,5].…”
Section: Discussionmentioning
confidence: 99%